Alloy and method for producing the same
Patent Information
- Application Number
- CN202611123602.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本申请实施例提供一种合金及其制备方法,以解决或缓解上面提出的一项或更多项技术问题
[0007]本申请实施例的合金兼具较高的强度和较好的韧性,尤其在高温条件下仍具有较高的强度和较好的韧性。具体地,第一尺寸的γ’析出相可以提供高密度的位错切割障碍,提供合金强度;第二尺寸的γ’析出相可以均匀化应变分布,避免局部应变集中,第一尺寸的γ’析出相和第二尺寸的γ’析出相协同,使合金兼具高温强度和韧性。在所述奥氏体组织内部具有多峰尺寸分布的γ’析出相,可以降低γ’析出相过度聚集,减少热应力集中。
Smart Images

Figure CN122918459A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of heat treatment technology, and in particular to an alloy and its preparation method. Background Technology
[0002] The impeller is the core component of the compressor and operates under harsh conditions. It not only bears the centrifugal stress generated by high-speed rotation and the vibration stress during rotation, but also the influence of low and high temperature environmental factors. Therefore, as the heart component of the centrifugal compressor, the impeller material must not only have high comprehensive mechanical properties and fatigue resistance, but also have low and high temperature mechanical properties according to the impeller's service conditions.
[0003] GH2132 is an Fe-25Ni-15Cr based superalloy, strengthened by the addition of molybdenum, titanium, aluminum, vanadium, and trace amounts of boron. It exhibits high yield strength and creep strength below 650℃, along with good machinability and satisfactory weldability. It is suitable for manufacturing high-temperature load-bearing components for aero-engines that operate continuously below 650℃, such as turbine disks, compressor disks, rotor blades, and fasteners. With the increasing demands on compressors, impeller speeds are rising, thus requiring higher yield strength and toughness. However, current GH2132 alloys struggle to simultaneously possess both high-temperature yield strength and toughness.
[0004] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of protection of this application. Summary of the Invention
[0005] This application provides an alloy and a method for preparing the same, in order to solve or alleviate one or more of the technical problems mentioned above.
[0006] A first aspect of the embodiments of this application is to provide an alloy. The alloy comprises Ni: 24.0wt%-27.0wt%, C: ≤0.05wt%, Cr: 13.5wt%-16.0wt%, Ti: 1.95wt%-2.35wt%, Al: ≤0.35wt%, Mn: 1.2wt%-2.0wt%, Mo: 1.0wt%-1.5wt%, Si: ≤1.0wt%, P: ≤0.0025wt%, S: ≤0.015wt%, B: 0.001wt%-0.01wt%, with the balance being Fe and unavoidable impurities. The alloy has an austenitic structure with γ' precipitates of gradient size within the austenitic structure. The first size of the γ' precipitates has a particle size of 30nm-50nm, and the second size of the γ' precipitates has a particle size of 15nm-30nm. Based on the total volume of the alloy, the volume fraction of the γ' precipitates is 3%-6.5%.
[0007] The alloy of this application embodiment possesses both high strength and good toughness, especially maintaining high strength and good toughness under high temperature conditions. Specifically, the first-sized γ' precipitates provide a high-density dislocation cutting barrier, contributing to the alloy's strength; the second-sized γ' precipitates homogenize the strain distribution, preventing localized strain concentration. The first-sized and second-sized γ' precipitates work synergistically, enabling the alloy to possess both high-temperature strength and toughness. The γ' precipitates with a multi-peak size distribution within the austenitic structure can reduce excessive aggregation of γ' precipitates and decrease thermal stress concentration.
[0008] According to an embodiment of this application, the austenitic structure contains γ' precipitates with a bimodal size gradient distribution, wherein the first-sized γ' precipitates have a particle size of 30nm-50nm and a volume fraction of 1.5%-2.5%; the second-sized γ' precipitates have a particle size of 15nm-30nm and a volume fraction of 1.5%-2.5%.
[0009] According to embodiments of this application, the third-sized γ' precipitate has a particle size of less than 10 nm. This further enhances the overall performance of the alloy.
[0010] According to an embodiment of this application, the austenitic structure contains γ' precipitates with a three-peak size gradient distribution, wherein the first-sized γ' precipitates have a particle size of 30nm-50nm and a volume fraction of 1.5%-2.5%; the second-sized γ' precipitates have a particle size of 15nm-30nm and a volume fraction of 1.5%-2.5%; and the third-sized γ' precipitates have a particle size of less than 10nm and a volume fraction of 0.5%-1.5%.
[0011] According to embodiments of this application, the alloy has a tensile strength of at least 930 MPa at 400°C, an elongation of at least 15.2% at 400°C, and a room temperature toughness Kv2 of at least 42 J.
[0012] A second aspect of this application provides a method for preparing the alloy described in the first aspect. The method includes the following steps: A target alloy is provided, comprising Ni: 24.0wt%-27.0wt%, C: ≤0.05wt%, Cr: 13.5wt%-16.0wt%, Ti: 1.95wt%-2.35wt%, Al: ≤0.35wt%, Mn: 1.2wt%-2.0wt%, Mo: 1.0wt%-1.5wt%, Si: ≤1.0wt%, P: ≤0.0025wt%, S: ≤0.015wt%, B: 0.001wt%-0.01wt%, with the balance being Fe and unavoidable impurities; The target alloy is subjected to isothermal annealing, wherein the isothermal annealing is performed by heating to 880℃-920℃ at a rate of no more than 200℃ / h, holding at that temperature for 2h-4h, then cooling to 690℃-730℃ at a rate of no more than 50℃ / h, holding at that temperature for at least 8h, and then air cooling to obtain the first intermediate part. The first intermediate component is subjected to a solution treatment, wherein the solution treatment involves heating to 940℃-960℃ at a rate not exceeding 150℃ / h, holding at that temperature for 1h-3h, and then water cooling to obtain the second intermediate component. The second intermediate component is subjected to a first aging treatment, which is performed at 710℃-730℃ for 16h-20h followed by air cooling to obtain the third intermediate component. The third intermediate component is subjected to a second aging treatment, wherein the conditions for the second aging treatment are 710℃-730℃, held at the temperature for 16h-20h, and then air-cooled to obtain the alloy.
[0013] The preparation method of this application embodiment first uses isothermal annealing to austenitize the material at the annealing temperature, obtaining a uniform microstructure; then, it forms precipitates by holding at 690℃-730℃, which disperses the segregation and aggregation that occurs in the matrix structure during melting, forging, etc., optimizes the uniformity of the material structure, and improves the strength of the material; in addition, the first aging treatment and the second aging treatment are performed at 710℃-730℃, and the amount of γ' precipitates and the grain size (such as the first size, the second size and / or the third size) are well matched. If the temperature of the first aging treatment and the second aging treatment is controlled below 700℃, the γ' precipitates will not precipitate sufficiently, and the strengthening degree of the alloy will be insufficient. If the temperature of the first and second aging treatments is too high, i.e. above 730℃, the strength of the alloy will decrease due to the aggregation and growth of the γ' precipitate and the precipitation of some η phase. By performing two aging treatments under the same conditions, the precipitation and growth of the γ' precipitate can be further promoted, thereby making the distribution of the γ' precipitate in the alloy more uniform, avoiding excessive aggregation of the γ' precipitate, and reducing thermal stress concentration.
[0014] According to an embodiment of this application, after the second aging treatment and before obtaining the alloy, a third aging treatment is further included. The conditions for the third aging treatment are: holding at 600℃-660℃ for 16h-20h followed by air cooling. This improves the three-peak distribution of the γ' precipitate size within the austenite, thereby enhancing the overall performance of the alloy.
[0015] According to an embodiment of this application, a hot charging furnace is used in the isothermal annealing process and the solution treatment process, and the temperature of the hot charging furnace is not greater than 700°C.
[0016] According to an embodiment of this application, the hot charging temperature during the isothermal annealing process is 180℃-300℃; the hot charging temperature during the solution treatment process is 120℃-200℃.
[0017] According to an embodiment of this application, the alloy is used for compressor impellers. The alloy of this application has good overall performance and is particularly suitable for compressor impellers. Attached Figure Description
[0018] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.
[0019] Figure 1 This is a microstructure diagram of the alloy from Example 2.
[0020] Figure 2 This is a TEM image of the alloy from Example 2. Detailed Implementation
[0021] The embodiments of this application are described in detail below with reference to the accompanying drawings. These embodiments are exemplary and are only used to explain this application, and should not be construed as limiting this application. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other.
[0022] It should be understood that when an element or layer is referred to as "on," "adjacent to," "connected to," or "coupled to" other elements or layers, it may be directly on, adjacent to, connected to, or coupled to other elements or layers, or there may be intervening elements or layers. Conversely, when an element is referred to as "directly on," "directly adjacent to," "directly connected to," or "directly coupled to" other elements or layers, there are no intervening elements or layers. It should be understood that although the terms first, second, third, etc., may be used to describe various elements, components, areas, layers, and / or portions, these elements, components, areas, layers, and / or portions should not be limited by these terms. These terms are only used to distinguish one element, component, area, layer, or portion from another element, component, area, layer, or portion. Therefore, without departing from the teachings of this application, the first element, component, area, layer, or portion discussed below may be referred to as a second element, component, area, layer, or portion. And the discussion of a second element, component, area, layer, or portion does not imply that the first element, component, area, layer, or portion necessarily exists in this application.
[0023] It should be noted that the terms "first," "second," etc., used in this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0024] In this application, when numerical intervals (i.e., numerical ranges) are involved, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0025] A first aspect of the embodiments of this application is to provide an alloy. The alloy comprises Ni: 24.0wt%-27.0wt%, C: ≤0.05wt%, Cr: 13.5wt%-16.0wt%, Ti: 1.95wt%-2.35wt%, Al: ≤0.35wt%, Mn: 1.2wt%-2.0wt%, Mo: 1.0wt%-1.5wt%, Si: ≤1.0wt%, P: ≤0.0025wt%, S: ≤0.015wt%, B: 0.001wt%-0.01wt%, with the balance being Fe and unavoidable impurities. The alloy has an austenitic structure with γ' precipitates of gradient size within the austenitic structure. The first size of the γ' precipitates has a particle size of 30nm-50nm, and the second size of the γ' precipitates has a particle size of 15nm-30nm. Based on the total volume of the alloy, the volume fraction of the γ' precipitates is 3%-6.5%.
[0026] The alloy of this application embodiment possesses both high strength and good toughness, especially maintaining high strength and good toughness under high temperature conditions. Specifically, the first-sized γ' precipitates provide a high-density dislocation cutting barrier, contributing to the alloy's strength; the second-sized γ' precipitates homogenize the strain distribution, avoiding local strain concentration. The first-sized and second-sized γ' precipitates work synergistically, enabling the alloy to possess both high-temperature strength and toughness. The γ' precipitates with a multi-peak size distribution within the austenitic structure reduce excessive aggregation of γ' precipitates, decrease thermal stress concentration, and at grain boundaries, the γ' precipitates exhibit a discontinuous granular distribution, without continuous chain-like or film-like brittle phases at the grain boundaries. In the elemental composition of the alloy, the lower limit of Ti is increased: Ti is the core forming element of γ' precipitates, and a higher Ti content can precipitate more and more stable dispersed spherical γ' precipitates, which have a stronger pinning effect on dislocations; the upper limit of Al is decreased: Al is a secondary γ' precipitate component, and lowering the upper limit of Al achieves a strength-plasticity balance. High Al tends to cause the γ' precipitates to have higher hardness and a decrease in the plasticity reserve of the matrix; the lower limit of Mn is increased: Mn dissolves into the γ' precipitate matrix to slightly increase the matrix strength, stabilize the austenite structure, suppress high-temperature phase transformation, and help improve dimensional stability; the upper limit of P is decreased: P segregation forms low-melting-point phosphide grain boundary films, which are prone to intergranular cracking under high-temperature stress, and P will strongly reduce the toughness of austenite and increase the tendency for cold brittleness. The upper limit of sulfur (S) is lowered: the NiS and FeS eutectic formed by S has an extremely low melting point, making it easily melted within the forging, heat treatment, and welding temperature ranges, inducing intergranular tearing; sulfide inclusions are fatigue crack initiation sources; S segregation weakens grain boundary bonding strength, preferentially generating intergranular voids and cracks under high-temperature creep. The volume fraction of γ' precipitates is 3%-6.5%, reducing alloy property fluctuations caused by over-aging or under-aging.
[0027] In some embodiments, the austenitic structure contains γ' precipitates with a bimodal size gradient distribution, wherein the first-sized γ' precipitates have a particle size of 30nm-50nm and a volume fraction of 1.5%-2.5%; the second-sized γ' precipitates have a particle size of 15nm-30nm and a content of 1.5%-2.5%.
[0028] In some embodiments, the alloy further includes third-sized γ' precipitates with a particle size of less than 10 nm. Under high stress, the third-sized γ' precipitates can undergo a certain degree of plastic deformation or bypass mechanism, absorbing energy and delaying crack initiation. Compared to a bimodal distribution, the trimodal distribution offers superior strength-toughness matching, especially under high stress or impact loads, where the third-sized γ' precipitates can act as a primary energy dissipation point, further enhancing impact toughness and fatigue resistance.
[0029] Furthermore, the austenitic microstructure contains γ' precipitates with a three-peaked size gradient distribution. The first-sized γ' precipitates have a particle size of 30 nm-50 nm and a volume fraction of 1.5%-2.5%. The second-sized γ' precipitates have a particle size of 15 nm-30 nm and a volume fraction of 1.5%-2.5%. The third-sized γ' precipitates have a particle size less than 10 nm and a volume fraction of 0.5%-1.5%. Through precise heat treatment, precipitation strengthening, critical size strengthening, and slip behavior regulation mechanisms are simultaneously activated. This design overcomes the limitations of single-size precipitates, improving the alloy's high-temperature strength, plasticity, creep resistance, and fatigue resistance, resulting in superior overall performance.
[0030] In some embodiments, the alloy has a tensile strength of at least 930 MPa at 400°C, an elongation of at least 15.2% at 400°C, and a room temperature toughness Kv2 of at least 42 J. The alloy of this application embodiment possesses sufficient strength to resist deformation at high temperatures and sufficient plasticity to avoid brittle fracture, while also exhibiting good impact resistance at room temperature.
[0031] Furthermore, the alloy has a tensile strength of at least 950 MPa at 550°C, an elongation of at least 16.7% at 400°C, and a room temperature toughness Kv2 of at least 48 J.
[0032] A second aspect of this application provides a method for preparing an alloy. The method includes the following steps: (1) Provide a target alloy comprising Ni: 24.0wt%-27.0wt%, C: ≤0.05wt%, Cr: 13.5wt%-16.0wt%, Ti: 1.95wt%-2.35wt%, Al: ≤0.35wt%, Mn: 1.2wt%-2.0wt%, Mo: 1.0wt%-1.5wt%, Si: ≤1.0wt%, P: ≤0.0025wt%, S: ≤0.015wt%, B: 0.001wt%-0.01wt%, with the balance being Fe and unavoidable impurities; (2) The target alloy is subjected to isothermal annealing, wherein the isothermal annealing is performed by heating to 880℃-920℃ at a rate of no more than 200℃ / h, holding for 2h-4h, cooling to 690℃-730℃ at a rate of no more than 50℃ / h, holding for at least 8h, and then air cooling to obtain the first intermediate part. (3) The first intermediate is subjected to solution treatment, wherein the solution treatment is performed by heating to 940℃-960℃ at a rate of no more than 150℃ / h, holding for 1h-3h and then water cooling to obtain the second intermediate; (4) The second intermediate component is subjected to a first aging treatment, wherein the conditions for the first aging treatment are 710℃-730℃, heat preservation for 16h-20h, followed by air cooling, to obtain the third intermediate component; (5) The third intermediate component is subjected to a second aging treatment. The conditions for the second aging treatment are 710℃-730℃, heat treatment for 16h-20h, followed by air cooling, in order to obtain the alloy.
[0033] The preparation method of this application embodiment first uses isothermal annealing to austenitize the material at the annealing temperature, obtaining a uniform microstructure; then, it forms precipitates by holding at 690℃-730℃, which disperses the segregation and aggregation that occurs in the matrix structure during melting, forging, etc., optimizes the uniformity of the material structure, and improves the strength of the material; in addition, the first aging treatment and the second aging treatment are performed at 710℃-730℃, and the amount of γ' precipitates and the grain size (such as the first size, the second size and / or the third size) are well matched. If the temperature of the first aging treatment and the second aging treatment is controlled below 700℃, the γ' precipitates will not precipitate sufficiently, and the strengthening degree of the alloy will be insufficient. If the temperature of the first and second aging treatments is too high, i.e. above 730℃, the strength of the alloy will decrease due to the aggregation and growth of the γ' precipitate and the precipitation of some η phase. By performing two aging treatments under the same conditions, the precipitation and growth of the γ' precipitate can be further promoted, thereby making the distribution of the γ' precipitate in the alloy more uniform, avoiding excessive aggregation of the γ' precipitate, and reducing thermal stress concentration.
[0034] According to an embodiment of this application, step (1) provides a target alloy. The target alloy comprises Ni: 24.0wt%-27.0wt%, C: ≤0.05wt%, Cr: 13.5wt%-16.0wt%, Ti: 1.95wt%-2.35wt%, Al: ≤0.35wt%, Mn: 1.2wt%-2.0wt%, Mo: 1.0wt%-1.5wt%, Si: ≤1.0wt%, P: ≤0.0025wt%, S: ≤0.015wt%, B: 0.001wt%-0.01wt%, with the balance being Fe and unavoidable impurities.
[0035] The alloy composition is limited to the ranges mentioned above, with stricter ranges for C, P, and S, and a lower limit for Mn is defined, while the range for Ti is narrowed.
[0036] According to an embodiment of this application, step (2) involves isothermal annealing the target alloy. The isothermal annealing involves heating to 880℃-920℃ at a rate not exceeding 200℃ / h (e.g., 50℃ / h, 100℃ / h, 150℃ / h, 200℃ / h, etc.), holding at that temperature for 2-4 hours, then cooling to 690℃-730℃ at a rate not exceeding 50℃ / h (e.g., 10℃ / h, 20℃ / h, 30℃ / h, 40℃ / h, 50℃ / h, etc.), holding at that temperature for at least 8 hours, and then air-cooling to obtain the first intermediate component.
[0037] In some embodiments, the isothermal annealing treatment can be performed using a hot-charging furnace, wherein the temperature of the hot-charging furnace does not exceed 700°C. This reduces thermal stress cracking in the target alloy and decreases notch sensitivity.
[0038] Furthermore, the hot charging temperature during the isothermal annealing process is 180℃-300℃, for example, 180℃, 200℃, 220℃, 250℃, 280℃, 300℃.
[0039] According to the embodiments of this application, step (3) involves performing a solution treatment on the first intermediate component, wherein the solution treatment involves heating the component to 940°C-960°C at a rate not exceeding 150°C / h, holding it at that temperature for 1-3 hours, and then water cooling it to obtain the second intermediate component.
[0040] In some embodiments, a hot-charging furnace is used in the solution treatment, and the temperature of the hot-charging furnace does not exceed 700°C. This reduces thermal stress cracking in the first intermediate component and decreases notch sensitivity.
[0041] Furthermore, the hot charging temperature during the solution treatment process is 120℃-200℃, for example, 120℃, 140℃, 160℃, 180℃, 200℃, etc.
[0042] According to the embodiments of this application, step (4) involves performing a first aging treatment on the second intermediate component. The conditions for the first aging treatment are 710℃-730℃, such as 700℃, 710℃, 720℃, 730℃, etc., and keeping it at that temperature for 16h-20h (e.g., 16h, 17h, 18h, 19h, 20h, etc.) before air cooling to obtain the third intermediate component.
[0043] In some embodiments, the temperature of the second intermediate component entering the furnace is no greater than 250°C. This reduces thermal stress cracking of the second intermediate component and decreases notch sensitivity.
[0044] According to an embodiment of this application, step (5) involves performing a second aging treatment on the third intermediate component. The conditions for the second aging treatment are: holding at 710℃-730℃ for 16h-20h followed by air cooling to obtain the alloy.
[0045] The first and second aging treatments described above are under the same process conditions. In the first aging treatment, the nucleation sites of the γ' precipitate phase in the supersaturated solid solution are activated and grow after solid solution treatment. The air cooling process allows some of the incompletely precipitated alloying elements to remain in the solid solution. In the second aging treatment, the existing γ' precipitate phase continues to grow slowly, forming a multi-peak size distribution and reducing notch sensitivity.
[0046] In some embodiments, step (6) further includes a third aging treatment after the second aging treatment and before obtaining the alloy. The conditions for the third aging treatment are: holding at 600℃-660℃ for 16h-20h followed by air cooling. In this step, the γ' precipitate is further promoted to continue to grow slowly, forming a three-peak size distribution and reducing notch sensitivity.
[0047] In some embodiments, the alloy is a compressor impeller. Compressor impellers require superior comprehensive mechanical properties and fatigue resistance, as well as high-temperature and low-temperature mechanical properties. The alloy of this application is formed through the aforementioned steps, giving it excellent mechanical properties, making it particularly suitable for compressor impellers. Furthermore, the compressor impeller can be used in extreme operating conditions such as aerospace, energy, and chemical industries.
[0048] Exemplary embodiments according to this application will now be described in more detail with reference to the accompanying drawings. It should be understood that these exemplary embodiments may be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0049] Example 1 Isothermal annealing: The target alloy (Ni: 25.02wt%, C: 0.028wt%, Cr: 14.62wt%, Ti: 1.98wt%, Al: 0.2wt%, Mn: 1.48wt%, Si: 0.22wt%, P: 0.011wt%, S: 0.001wt%, B: 0.0027wt%, Mo: 1.23wt%, balance Fe and unavoidable impurities) was loaded into the furnace at 220℃, heated at 120℃ / h to 900℃, held for 2h, then cooled to 710℃ at a rate of 50℃ / h and held for 8h, and then removed from the furnace and air-cooled.
[0050] Solution treatment; load the furnace at 200℃, raise the temperature at 100℃ / h to 950℃, hold for 1 hour, and then remove from the furnace and water cool.
[0051] First aging treatment: Heat to 720℃, hold for 16 hours, then remove from the furnace and air cool.
[0052] Second aging treatment: Heat to 720℃, hold for 16 hours, then remove from the furnace and air cool.
[0053] Example 2 Isothermal annealing: The target alloy (Ni: 25.02wt%, C: 0.028wt%, Cr: 14.62wt%, Ti: 1.98wt%, Al: 0.2wt%, Mn: 1.48wt%, Si: 0.22wt%, P: 0.011wt%, S: 0.001wt%, B: 0.0027wt%, Mo: 1.23wt%, balance Fe and unavoidable impurities) was loaded into the furnace at 180℃, heated at 100℃ / h to 910℃, held for 3h, then cooled to 720℃ at 42℃ / h and held for 10h, and then removed from the furnace and air-cooled.
[0054] Solution treatment; load the furnace at 120℃, raise the temperature at 80℃ / h to 960℃, hold for 2 hours, and then remove from the furnace and cool with water.
[0055] First aging treatment: Heat to 718℃, hold for 18 hours, then remove from the furnace and air cool.
[0056] Second aging treatment: Heat to 715℃, hold for 20 hours, then remove from the furnace and air cool.
[0057] Third aging treatment: Heat to 650℃, keep warm for 20 hours, then remove from the furnace and air cool.
[0058] Comparative Example 1 Solution treatment: The target alloy (Ni: 25.02wt%, C: 0.028wt%, Cr: 14.62wt%, Ti: 1.98wt%, Al: 0.2wt%, Mn: 1.48wt%, Si: 0.22wt%, P: 0.011wt%, S: 0.001wt%, B: 0.0027wt%, Mo: 1.23wt%, balance Fe and unavoidable impurities) was loaded into the furnace at 220℃, heated at 90℃ / h to 950℃, held at that temperature for 2h, and then removed from the furnace and air-cooled.
[0059] Aging treatment: Heat to 710℃, hold for 16 hours, then remove from the furnace and air cool.
[0060] The alloys of the above embodiments and comparative examples were tested as follows, and the results are shown in Table 1.
[0061] Tensile test: The test conditions are as follows: The high temperature tensile test is conducted using the Taiwan High Speed Rail AI-7000-LAU10 tensile testing machine, and the test method is GB / T 228.2-2015 "Metallic materials, tensile testing - Part 2: High temperature test method".
[0062] Toughness test: The test conditions are as follows: The impact test is conducted using a pendulum impact testing machine produced by Shenzhen Lanbo Sansi Materials Testing Co., Ltd. The Charpy V-notch specimen has the following nominal dimensions: total length 55 mm, cross-section is square with side length of 10 mm × 10 mm, and the test method is GB / T 229-2020 "Metallic Materials Charpy Pendulum Impact Test Method".
[0063] Table 1
[0064] In Table 1, / indicates that no relevant performance tests were conducted on the alloy.
[0065] As shown in Table 1 above, the high-temperature strength of the GH2132 alloy prepared in this application is higher than that of the comparative example, the plasticity change is not obvious, and the toughness is only slightly reduced. Among them, Example 2 shows excellent hot strength, with a small strength reduction in the temperature range of 400℃-550℃ and stable high-temperature strength. The yield strength of the alloy of this invention at 400℃-550℃ can reach 730MPa and 767MPa, and the tensile strength reaches 932MPa and 974MPa, with a yield strength ratio as high as 78%-80%, which is consistent with the typical characteristics of precipitation-strengthened alloys. This indicates that the γ'-Ni3Ti strengthening phase is finely dispersed and coherently precipitated in the crystal, which effectively hinders dislocation shear by generating a high-density coherent strain field, and the precipitation strengthening effect is significant. It is generally recognized in the field of materials that a high yield strength ratio at high temperature can significantly improve its structural stability, creep resistance and long-term safety redundancy in high-temperature service environments, while realizing efficient utilization of material strength and lightweight component design. Therefore, the alloy of this application has irreplaceable engineering value in extreme working conditions such as aviation, energy and chemical industries.
[0066] Figure 1 This is a microstructure diagram of the alloy in Example 2. As can be seen from the diagram, the alloy is composed of austenitic structure and uniformly distributed carbides. Twins can be observed in the austenitic grains, with a grain size of grade 5.
[0067] Figure 2 The image shows the TEM image of the alloy in Example 2. As can be seen from the image, the precipitates of the alloy are distributed in a multi-scale gradient. The size characteristics are: a multi-peak distribution including larger γ' (15-30nm) and (30-50nm) formed in the first two aging processes and smaller γ' (<10nm) precipitated in the third aging process, forming a gradient strengthening field. The volume fraction of γ' (30-50nm) is 2%, the volume fraction of γ' (15-30nm) is 2%, and the volume fraction of γ' (<10nm) is 1%.
[0068] It should also be noted that the terms "some embodiments," "other embodiments," and "embodiments" used in this application refer to specific features, structures, or characteristics described in connection with those embodiments, which are included in at least one embodiment described in the general description of this application. The appearance of the same expression in multiple places in the specification does not necessarily refer to the same embodiment. Furthermore, when a specific feature, structure, or characteristic is described in connection with any embodiment, the intention is to suggest that implementing such a feature, structure, or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0069] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0070] It should also be noted that the above are merely preferred embodiments of this application and do not limit the scope of protection of this application. Any equivalent structural or procedural transformations made using the content of this application specification, or direct or indirect applications in other related technical fields, are similarly included within the scope of protection of this application.
Claims
1. An alloy, characterized in that, include: Ni: 24.0wt%-27.0wt%, C: ≤0.05wt%, Cr: 13.5wt%-16.0wt%, Ti: 1.95wt%-2.35wt%, Al: ≤0.35wt%, Mn: 1.2wt%-2.0wt%, Mo: 1.0wt%-1.5wt%, Si: ≤1.0wt%, P: ≤0.0025wt%, S: ≤0.015wt%, B: 0.001wt%-0.01wt%, balance Fe and unavoidable impurities; The alloy has an austenitic structure, within which there are γ' precipitates with a gradient size distribution, wherein the first size of the γ' precipitates has a particle size of 30nm-50nm, and the second size of the γ' precipitates has a particle size of 15nm-30nm. Based on the total volume of the alloy, the volume fraction of the γ' precipitate is 3%-6.5%.
2. The alloy according to claim 1, characterized in that, The austenitic structure contains γ' precipitates with a bimodal size gradient distribution, wherein the first-sized γ' precipitates have a particle size of 30nm-50nm and a volume fraction of 1.5%-2.5%. The particle size of the second-sized γ' precipitate is 15nm-30nm, and the volume fraction of the second-sized γ' precipitate is 1.5%-2.5%.
3. The alloy according to claim 1, characterized in that, Also includes: The particle size of the third-sized γ' precipitate is less than 10 nm.
4. The alloy according to claim 3, characterized in that, The austenitic structure contains γ' precipitates with a three-peak size gradient distribution, wherein the first-sized γ' precipitates have a particle size of 30nm-50nm and a volume fraction of 1.5%-2.5%. The particle size of the second-sized γ' precipitate is 15nm-30nm, and the volume fraction of the second-sized γ' precipitate is 1.5%-2.5%. The particle size of the third-size γ' precipitate is less than 10 nm, and the volume fraction of the third-size γ' precipitate is 0.5%-1.5%.
5. The alloy according to any one of claims 1-4, characterized in that, The alloy has a tensile strength of at least 930 MPa at 400°C, an elongation of at least 15.2% at 400°C, and a room temperature toughness Kv2 of at least 42 J.
6. A method for preparing the alloy according to any one of claims 1-5, characterized in that, Includes the following steps: A target alloy is provided, comprising Ni: 24.0wt%-27.0wt%, C: ≤0.05wt%, Cr: 13.5wt%-16.0wt%, Ti: 1.95wt%-2.35wt%, Al: ≤0.35wt%, Mn: 1.2wt%-2.0wt%, Mo: 1.0wt%-1.5wt%, Si: ≤1.0wt%, P: ≤0.0025wt%, S: ≤0.015wt%, B: 0.001wt%-0.01wt%, with the balance being Fe and unavoidable impurities; The target alloy is subjected to isothermal annealing, wherein the isothermal annealing is performed by heating to 880℃-920℃ at a rate of no more than 200℃ / h, holding at that temperature for 2h-4h, then cooling to 690℃-730℃ at a rate of no more than 50℃ / h, holding at that temperature for at least 8h, and then air cooling to obtain the first intermediate part. The first intermediate component is subjected to a solution treatment, wherein the solution treatment involves heating to 940℃-960℃ at a rate not exceeding 150℃ / h, holding at that temperature for 1h-3h, and then water cooling to obtain the second intermediate component. The second intermediate component is subjected to a first aging treatment, which is performed at 710℃-730℃ for 16h-20h followed by air cooling to obtain the third intermediate component. The third intermediate component is subjected to a second aging treatment, wherein the conditions for the second aging treatment are 710℃-730℃, held at the temperature for 16h-20h, and then air-cooled to obtain the alloy.
7. The preparation method according to claim 6, characterized in that, After the second aging treatment and before obtaining the alloy, a third aging treatment is further included. The conditions for the third aging treatment are: heat preservation at 600℃-660℃ for 16h-20h followed by air cooling.
8. The preparation method according to claim 6 or 7, characterized in that, The isothermal annealing process and the solution treatment process are carried out in a hot charging furnace, and the temperature of the hot charging furnace is not greater than 700°C.
9. The preparation method according to claim 8, characterized in that, The hot charging temperature during the isothermal annealing process is 180℃-300℃; The hot charging temperature during the solution treatment process is 120℃-200℃.
10. The preparation method according to any one of claims 7-9, characterized in that, The alloy is used for compressor impellers.